The grammatical class effect is separable from the concreteness effect in language learning. Issue 3 (20th May 2020) - Martin, Katherine I.; Tokowicz, Natasha
Abstract: Typically concrete words are learned better than abstract words (Kaushanskaya & Rechtzigel, 2012), and nouns are learned better than verbs (Kauschke & Stenneken, 2008). However, most studies on concreteness have not manipulated grammatical class (and vice versa), leaving the relationship between the two unclear. Therefore, in two experiments we examined the effects of grammatical class and concreteness simultaneously in foreign language vocabulary learning. In Experiment 1, English speakers learned 'foreign language' words (English pseudowords) mapped to concrete and abstract nouns and verbs. In Experiment 2, English speakers learned German words with the same procedure. Overall, the typical advantages for concrete words and nouns were observed. Hierarchical regression analyses provided evidence that the grammatical class effect is separable from the concreteness effect. This result challenges a strict concreteness-based source of noun/verb differences. The results also suggest that the influences of concreteness and grammatical class may vary across language measures and tasks.